A Hybrid Model for Power Consumption Forecasting Using VMD-Based the Long Short-Term Memory Neural Network - Ruan, Yingjun; Wang, Gang; Meng, Hua; Qian, Fanyue (Frontiers in Energy Research, 2022)
Energy consumption prediction is a popular research field in computational intelligence. However, it is difficult for general machine learning models to handle complex time series data such as building energy consumption data, and the results are often unsatisfactory. To address this difficulty, a hybrid prediction model based on modal decomposition was proposed in this paper. For data preprocessing, the variational mode decomposition (VMD) technique was used to used to decompose the original sequence into more robust subsequences. In the feature selection ,the maximum relevance minimum redundancy(mRMR) algorithm was chosen to analyse the correlation between each component and the individual features while eliminating the redundancy between individual features. In the forecasting module, the long short-term memory (LSTM) neural network model was used to predict power consumption. In order to verify the performance of the proposed model, three categories of contrast methods were applied:(1) Comparing the hybrid model to a single predictive model, (2) Comparing the hybrid model with the backpropagation neural network (BPNN) to the hybrid model with the LSTM and (3) Comparing the hybrid model using mRMR and the hybrid model using mutual information maximization (MIM). The experimental results on the measured data of an office building in Qingdao show that the proposed hybrid model can improve the prediction accuracy and has better robustness compared to VMD-MIM-LSTM. In the three control groups mentioned above, the R2 value of the hybrid model improved by 10%, 3% and 3%, respectively, the values of the mean absolute error (MAE) decreased by 48.9%, 41.4% and 35.6%, respectively, and the root mean square error (RMSE) decreased by 54.7%, 35.5% and 34.1%, respectively.